GENOTOXICITY OF EXTRACT OF AGRICULTURAL SOIL COLLECTED NEAR THERMAL POWER PLANT - LALIT KUMAR GHOSH,; ABHA,; M. JHA, (International Journal of Pharma and Bio Sciences, 2012)
In the present study, by employing highly sensitive and simple plant bioassay, Allium cepa micronucleus test (MN test), genotoxicity of soil samples collected from the agricultural field near thermal power plant was evaluated. Roots of Allium cepa were treated with 10, 20. 30, 40 and 50% solution of extract of soil samples at room temperature in dark. Genotoxicity was expressed in terms of frequency of micronuclei in root tip cells. Treatment of roots caused concomitant increase in the frequency of micronuclei in root tip cells. The result shows that extract of soil induced genotoxic effect in the root tip cells which may be due to presence of heavy metals.